NEW SCALE INGIBITOR FOR OIL FIELDS - Tursunov, Maksad; Abdirazakov , Akmal; Norinov, Fakhriyor; Kenzhaev, Kudduz (Innovatsion texnologiyalar, 2024)
The article presents the results of laboratory tests of a new scale inhibitor designed to prevent deposits of sulfate and carbonate salts in oilfield equipment systems, pipelines during oil production and transportation. In order to determine the effectiveness of the protective action of the presented sample of scale inhibitor, studies were carried out on the formation water of the Chegara SP-1 field at various dosages. As a result of the research, the optimal dosage of the scale inhibitor for the Chegara field was established.